108k views
3 votes
Solve50q - 43 = 52q - 81

1 Answer

6 votes

hello

the question given to us is a simple algebraic equation and we can implore some simple steps to solve a problem like this.

step one

collect like terms

to do this, bring terms that are alike to one side of the equation and non-like terms in the opposite side of the equation. in this case, we bring the coefficient of q to one side and non-coefficient (numbers) to the other side of the equation.


\begin{gathered} 50q-43=52q-81 \\ -43+81=52q-50q \end{gathered}

notice how the sign changes from some variables like (-81 to +81) and (50q to -50q). The reason is that whenever a number, variable or basically anything crosses an equality sign (=, >, or <) the sign will have to change from positive to negative or negative to positive. and that's why we have a change in sign in this case.

step two

simplify

to do this, we simply need to add or subtract the values together on each side of the equation.


\begin{gathered} -43+81=52q-50q \\ 38=2q \end{gathered}

step three

divide both sides by the coefficient of q

in this case, we simply need to divide both sides by 2 in order to get the actually and true value of q. Only then we can say we've solved for q.


\begin{gathered} 38=2q \\ (38)/(2)=(2q)/(2) \\ 19=q \\ q=19 \end{gathered}

from the calculations above, the value of q is equal to 19

User Piyush Kansal
by
4.7k points